Using Stable Isotope Analyses to Assess the Trophic Ecology of Scleractinian Corals - Michael P. Lesser; Marc Slattery; Keir J. Macartney (Oceans, 2022)
Studies on the trophic ecology of scleractinian corals often include stable isotope analyses of tissue and symbiont carbon and nitrogen. These approaches have provided critical insights into the trophic sources and sinks that are essential to understanding larger-scale carbon and nitrogen budgets on coral reefs. While stable isotopes have identified most shallow water (<30 m) corals as mixotrophic, with variable dependencies on autotrophic versus heterotrophic resources, corals in the mesophotic zone (~30–150 m) transition to heterotrophy with increasing depth because of decreased photosynthetic productivity. Recently, these interpretations of the stable isotope data to distinguish between autotrophy and heterotrophy have been criticized because they are confounded by increased nutrients, reverse translocation of photosynthate, and changes in irradiance that do not influence photosynthate translocation. Here we critically examine the studies that support these criticisms and show that they are contextually not relevant to interpreting the transition to heterotrophy in corals from shallow to mesophotic depths. Additionally, new data and a re-analysis of previously published data show that additional information (e.g., skeletal isotopic analysis) improves the interpretation of bulk stable isotope data in determining when a transition from primary dependence on autotrophy to heterotrophy occurs in scleractinian corals.